Description of a new species of Priolepis (Perciformes: Gobiidae) from the Red Sea, a new record of Priolepis compita, and a distributional range extension of Trimma fishelsoni - Bogorodsky, Sergey V.; Suzuki, Toshiyuki; Mal, Ahmad O. (Zootaxa, 2016)
A new species of Reefgoby, Priolepis melanops, is described from Al Lith, central Saudi Arabian coast of the Red Sea, on the basis of a single adult specimen. It is a distinctive species, and can distinguish from its congeners by the following characters: dorsal-fin rays VI + I,9, no elongate spines in first dorsal fin; anal-fin rays I,8; pectoral-fin rays 14–15, all unbranched; longitudinal scale series 25; no scales on the head or predorsal midline, sides of the nape scaled; a developed transverse pattern of the sensory papillae below the eye; fifth pelvic-fin ray unbranched, its length 47% length of fourth ray; body and most of head brownish orange, densely covered with melanophores; snout, lips, chin and chest black; iris black; fins translucent with narrow black stripe along base of each dorsal fin. Placement of the new species in Priolepis is based on the presence of characteristics currently associated with Priolepis rather than with Trimma. An individual of Priolepis compita Winterbottom was photographed in very shallow water on a reef flat at Sharm el Sheikh, at the entrance of the Gulf of Aqaba, and represents a new record for the Red Sea. The endemic Red Sea species Trimma filamentosus Winterbottom and T. fishelsoni Goren, previously know as far south as Jeddah, were collected at Al Lith, central Saudi Arabia, and represents the southernmost record for both species. Variation of P. compita and T. fishelsoni is noted and the cephalic sensory system of the latter is described for the first time. In addition, we report that records of Trimma tevegae Cohen & Davis from the Red Sea are based on misidentification. A key to distinguish the species of Priolepis and Trimma known from the Red Sea is provided.